SCIENTISM AND EFFECTIVENESS IN TEACHING OF FOREIGN LANGUAGES: CONTENT AND LANGUAGE INTEGRATED LEARNING (CLIL) - Hrušková, Lenka; Krátká, Jana (PEOPLE: International Journal of Social Sciences, 2017)
The concept of language education process cannot be unilaterally practical nor impractically theoretical. The principle that practice is the criterion of truth of a theory is true also in the philosophy of the teaching process. This theoretically focused contribution gives a structured view on selected factors of teaching effectiveness, emphasizing pedagogical-psychological factors. The principle of scientism of the education system is analyzed from the point of view of psycho-didactics and language teaching methodology. Language teaching must fully accept the principle emphasized by the dynamics of the educational process by continuously updating knowledge, discovering contradictions and follow the principle of unity of theory and practice. In order for motivation to be a really effective factor of effectiveness, it is necessary to focus it on psycho-didactically relevant goals which are ideally set by the teacher together with their students The authors focus their attention on goal motivational orientation of language teaching which encourages and enables autonomous and self-directed student learning.